Maternal exposure to ambient air pollution and congenital heart defects in China. (August 2021) - Yang, Bo-Yi; Qu, Yanji; Guo, Yuming; Markevych, Iana; Heinrich, Joachim; Bloom, Michael S.; Bai, Zhipeng; Knibbs, Luke C.; Li, Shanshan; Chen, Gongbo; Jalaludin, Bin; Morawska, Lidia; et al.
Highlights: Maternal PM and NO2 exposure was associated with higher odds of CHD. The first trimester might be the critical exposure window of air pollution for CHD. Pattern of the associations of air pollutants with CHD subtypes was mixed. Abstract: Background: Evidence of maternal exposure to ambient air pollution on congenital heart defects (CHD) has been mixed and are still relatively limited in developing countries. We aimed to investigate the association between maternal exposure to air pollution and CHD in China. Method: This longitudinal, population-based, case-control study consecutively recruited fetuses with CHD and healthy volunteers from 21 cities, Southern China, between January 2006 and December 2016. Residential address at delivery was linked to random forests models to estimate maternal exposure to particulate matter with an aerodynamic diameter of ≤ 1 µm (PM1 ), ≤2.5 µm, and ≤10 µm as well as nitrogen dioxides, in three trimesters. The CHD cases were evaluated by obstetrician, pediatrician, or cardiologist, and confirmed by cardia ultrasound. The CHD subtypes were coded using the International Classification Diseases. Adjusted logistic regression models were used to assess the associations between air pollutants and CHD and its subtypes. Results: A total of 7055 isolated CHD and 6423 controls were included in the current analysis. Maternal air pollution exposures were consistently higher among cases than those among controls. Logistic regression analyses showed that maternal exposure to all air pollutants during the first trimester was associated with an increased odds of CHD (e.g., an interquartile range [13.3 µg/m 3 ] increase in PM1 was associated with 1.09-fold ([95% confidence interval, 1.01–1.18]) greater odds of CHD). No significant associations were observed for maternal air pollution exposures during the second trimester and the third trimester. The pattern of the associations between air pollutants and different CHD subtypes was mixed. Conclusions: Maternal exposure to greater levels of air pollutants during the pregnancy, especially the first trimester, is associated with higher odds of CHD in offspring. Further longitudinal well-designed studies are warranted to confirm our findings.